THE INFLUENCE OF PERCEIVED USEFULNESS, PERCEIVED EASE OF USE, AND PERCEIVED RISK ON PURCHASE INTERESTAND USE BEHAVIOR THROUGH BUKALAPAK APPLICATION IN SAMARINDA - Rizky Abdillah Isma; Syarifah Hudayah; Herning Indriastuti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study aims to analyze and explain the effect of perceived usefulness, perceived ease of use, and perceived risk on purchase interest and use behavior through the Bukalapak application in Samarinda. The data collection technique used is non-profitability sampling. A total of 105 respondents used in this study were those who had used the Bukalapak application located in the city of Samarinda, East Kalimantan. The e analysis is carried out using Partial Least Square (PLS) with the SmartPLS application version 3.8.9. The results showed that: Perceived Usefulness has a positive effect on purchase intention; Perceived ease of use has a positive influence on purchase intention; perceived risk has a positive effect on purchase intention; perceived usefulness has a positive influence on use behavior; perceived ease of use does not have a positive effect on use behavior; perceived risk has a positive influence on use behavior; Purchase intention has a positive influence on use behavior. Keywords: Perceived Usefulness, Perceived Ease of Use, Perceived Risk, Purchase Interest, Use Behavior